Pendampingan UMKM Desa Bojongsoang Kabupaten Bandung Melalui Inovasi Qris, Maps dan Branding untuk Meningkatkan Ekonomi Masyarakat - Hafsari, Sheila (Jurnal Pengabdian Tri Bhakti, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving local economic growth, particularly in rural areas. However, many MSMEs still face obstacles in digital adaptation, marketing, and brand development. This community service program was conducted in Bojongsoang Village, Bandung Regency, with the aim of strengthening MSME capacity through the implementation of QRIS (Quick Response Code Indonesian Standard), MAPS (digital mapping for business visibility), and branding innovation. The method employed was participatory, involving direct engagement with local MSME actors in four stages: preparation, implementation, output, and evaluation. Activities included training on digital payment systems, mapping MSME locations to increase accessibility, and developing simple yet effective branding strategies tailored to the potential of each business. The results showed that MSMEs were more confident in using QRIS for transactions, gained broader market reach through online mapping, and improved their business identity through branding. These outcomes not only enhanced operational efficiency but also increased consumer trust and competitiveness in the local market. The implication of this program highlights that digital innovation combined with participatory approaches can significantly empower rural MSMEs and contribute to sustainable economic development at the community level.